Patent and Technical Forensic Examination - Yu. V. Grigor’ev (Теория и практика судебной экспертизы)
The article provides recommendations based on the author’s personal experience on conducting patent and technical forensic examination of inventions and utility models. It complements the recently published educational and methodological manual, which highlights the legal norms and practical aspects of patent and technical expertise. The main sections of the article are devoted to the prevention of procedural violations, ensuring the sustainability of conclusions and are accompanied by a number of practical examples.